Ciclosporina A no eritema nodoso hansênico com manifestações sistêmicas: avaliação clínica, laboratorial e histopatológica - AZEVEDO, Maria do Socorro Marques (Universidade Federal do Pará, 2013)
The ENL is a severe and acute interference that attacks patients of lepromatous and borderline lepromatous leprosy forms from Ridley and Jopling classification. In this study, the immunomodulator drug cyclosporine A was used to evaluate its effectiveness in ENL reaction, whose treatment is based on the use of drugs as thalidomide that has several restrictions and that induce dependence among other damages. Ten ENL patients with systemic manifestations and more than two reactions episodes were chosen. These patients had taken high doses of corticosteroids during years and eight of they, took thalidomide more than three times too. All patients were followed clinically for 90 days and took 3-5 mg/kg/daily, besides they accomplish laboratory exams in the zero day, 15 th and 60 th of use cyclosporine A and made also hystopathologic exams (before and 60 days after cyclosporine A). It was requesting the next laboratory exams: blood-count; leuko-count; TGO; TGP; urea and creatinine. Among laboratory exams changes, there was leucocytosis in 70% of patients that was reduced until the end of follow up in the same percentage. Biochemical exams didn't show significance disturb, except for the increase of TGO in one patient and of TGP in another, besides two cases who showed increase of urea and creatinine, but later on, they were better without any additional assistance. In 40 % of patients, the first's hystopathologic exams, alterations were represented for granulomatosis dermatitis and in 30% of sick ones, for nodular dermatitis. In second exams, there was change to superficial and deep infiltration in the blood vessel walls, in 50 % of cases; septal panniculitis in 20 %. It denotes histological improvement verified in the first fifteen days of therapy. The cyclosporine A action was specially useful in systemic symptoms, except in the cases who had neuritis. Then, cyclosporine A can be an alternative for clinical improvement to leprosy reaction type II.